Beneficial effects of the treatment of iron deficiency on clinical condition, left ventricular function, and quality of life in patients with chronic heart failure - Mirdamadi, Ahmad; Arefeh, Asadolahi; Garakyaraghi, Mohammad; Pourmoghadas, Ali (Acta Biomedica Atenei Parmensis, 2018)
Background: Anemia is now considered as an important contributing factor to the deterioration of chronic heart failure. The present study aimed to assess the effects of intravenous iron therapy on clinical condition, left ventricular function and also quality of life in patients who suffered of chronic heart failure and concomitant iron deficiency. Methods: In this clinical trial, 25 consecutive patients with concomitant chronic heart failure and iron deficiency referred to Shariati hospital  in Isfahan, Iran in 2013. After initial clinical, laboratory, and echocardiography assessments, the patients administered 200 mg intravenous Iron per week until compensating iron deficit. Then, all study parameters were assessed again and compared to parameters before the therapeutic intervention. Results: The NYHA class showed a significant improvement after the therapeutic approach. The prevalence of heart failure-related edema was also significantly reduced from 60% before treatment to 48% after that (p = 0.036). The rate of hospitalization was considerably reduced from 42% to 16% (P < 0.001). Moreover, mean 6 minute walk test (6MWT) was increased from 155.18 m to 187.40 m (P < 0.001). Comparing Left Ventricular Ejection Fraction (LVEF) after treatment to figures before the test indicated a significant improvement in this parameter (27.5% versus 33.0%, P = 0.007). The treatment of iron deficiency in this group of subjects got a significant improvement in SF36 total score. Conclusion: In patients with chronic heart failure, the treatment of iron deficiency results in a marked improvement in functional status, ejection fraction, and also quality of life as well as a reduction in need to re-hospitalization, however renal function was deteriorated and thus more pay attention to renal function is necessary.